900 V/1.6 m Omega . cm(2) Normally Off Al2O3/GaN MOSFET on Silicon Substrate - Wang, Maojun; Wang, Ye; Zhang, Chuan; Xie, Bing; Wen, Cheng P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Chen, Kevin J.; Shen, Bo (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2014)
In this paper, we report the device performance of a high-voltage normally off Al2O3/GaN MOSFET on the Si substrate. Normally off operation is obtained by multiple cycles of O-2 plasma oxidation and wet oxide-removal gate recess process. The recessed normally off GaN MOSFET with 3 mu m gate-drain distance exhibits a maximum drain current of 585 mA/mm at 9 V gate bias. The threshold voltage of the MOSFET is 2.8 V with a standard derivation of 0.2 V on the sample with an area of 2 x 2 cm(2). The gate leakage current is below 10(-6) mA/mm during the whole gate swing up to 9 V and the I-ON/I-OFF ratio is larger than 10(9), indicating the good quality of Al2O3 gate insulator. The MOSFET with 10 mu m gate-drain distance shows a three terminal OFF-state breakdown voltage (BV) of 967 V at zero gate-source bias with a drain leakage current criterion of 1 mu A/mm. The specific ON-resistance (R-ON,R- SP) of the device is 1.6 m Omega . cm(2) and the power figure of merit (BV2/R-ON,R- SP) is 584 MW/cm(2).